Методика проведення цифрової криміналістичної експертизи месенджерів - Рєзніченко, Д. Ю.; Снігуров, А. В. (ХНУРЕ, 2023)
This work is devoted to research in the field of digital forensics, more specifically - forensics of modern messengers. This work briefly describes the internal structure of Viber, Telegram and WhatsApp messengers. Also, the methodology developed for their research is presented. In addition, this study shows examples of the use of the developed methodology for the search and research of messenger artifacts. It is worth noting that the method shown in this work is relevant only for Windows and Android operating systems.
Keywords: месенджер; криміналістична експертиза